CENP-C Is a Structural Platform for Kinetochore Assembly. - Przewloka, M.R.; Venkei, Z.; Bolanos-Garcia, V.M.; Debski, J.; Dadlez, M.; Glover, D.M. (Current Biology, 2011)
Centromeres provide a region of chromatin upon which kinetochores are assembled in mitosis. Centromeric protein C (CENP-C) is a core component of this centromeric chromatin that, when depleted, prevents the proper formation of both centromeres and kinetochores. CENP-C localizes to centromeres throughout the cell cycle via its C-terminal part, whereas its N-terminal part appears necessary for recruitment of some but not all components of the Mis12 complex of the kinetochore. We now find that all kinetochore proteins belonging to the KMN (KNL1/Spc105, the Mis12 complex, and the Ndc80 complex) network bind to the N-terminal part of Drosophila CENP-C. Moreover, we show that the Mis12 complex component Nnf1 interacts directly with CENP-C in vitro. To test whether CENP-C's N-terminal part was sufficient to recruit KMN proteins, we targeted it to the centrosome by fusing it to a domain of Plk4 kinase. The Mis12 and Ndc80 complexes and Spc105 protein were then all recruited to centrosomes at the expense of centromeres, leading to mitotic abnormalities typical of cells with defective kinetochores. Thus, the N-terminal part of Drosophila CENP-C is sufficient to recruit core kinetochore components and acts as the principal linkage between centromere and kinetochore during mitosis.